1981
DOI: 10.1128/aac.20.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bactericidal Activity of Moxalactam and Cefotaxime With and Without Tobramycin Against Pseudomonas aeruginosa and Staphylococcus aureus

Abstract: Serum bactericidal activity was determined against 10 strains each of Pseudomonas aeruginosa and Staphylococcus aureus in serum from volunteers 1 and 6 h after intravenous infusion of cefotaxime, tobramycin, and the combination; or of moxalactam, tobramycin, and the combination. High serum bactericidal activity against P. aeruginosa was found significantly more frequently with moxalactam plus tobramycin than with cefotaxime, moxalactam, and tobramycin alone or with cefotaxime plus tobramycin.Moxalactam (1-oxa-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…At 6 h, the combination was significantly more effective against all strains than was cefotaxime alone. Our data are comparable with those of other investigators who have shown a limited increase in the bactericidal activity of cefotaxime when aminoglycosides have been added (4 …”
supporting
confidence: 82%
See 2 more Smart Citations
“…At 6 h, the combination was significantly more effective against all strains than was cefotaxime alone. Our data are comparable with those of other investigators who have shown a limited increase in the bactericidal activity of cefotaxime when aminoglycosides have been added (4 …”
supporting
confidence: 82%
“…It is generally agreed upon that a bactericidal activity in serum of >1:8 correlates with the clinical effectiveness of antibiotics (3, 5a, 11), but in a recent review Wolfson and Swartz (12) have concluded that convincing proof of the utility of the bactericidal activity test in serum in the management of infective endocarditis is lacking. Lagast and co-workers studied the bactericidal activity in serum of cefotaxime alone and in association with tobramycin against clinical strains of Pseudomonas aeruginosa and Staphylococcus aureus (4). They observed increased activity of cefotaxime against both strains when used in combination with tobramycin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The bactericidal activity of moxalactam is generally reported as being equivalent to its inhibitory activity against P. aeruginosa (5,6,8,11,16). This assessment has, with a single exception (18), been based on the results of microdilution test procedures with inoculum sizes and subculture volumes which have been insufficient for an accurate determination of 99.9% killing (2,19).…”
mentioning
confidence: 99%